Pengetahuan dan Sikap Siswa SMA Terhadap Pemeriksaan Laboratorium dalam Penegakan Diagnosis Infeksi Menular Seksual di Provinsi Bali - Ni Made Sri Dwijastuti; Ni Putu Senshi Septiasari; IGAA Satwikha Dewi; I Wayan Tanjung Aryasa; Gde Palguna Reganata; Aprilia Rakhmawati (An-Nadaa : Jurnal Kesehatan Masyarakat (e-Journal), 2026)
Background: Enhancing laboratory-based early detection of sexually transmitted infections (STIs) is a critical element of STI control strategies. The effectiveness of diagnostic systems relies not only on technical capacity but also on population knowledge and acceptance of laboratory testing. Objective: To examine high school students’ knowledge and attitudes toward STI laboratory examinations according to respondent characteristics, serving as indicators of diagnostic literacy among adolescents. Methods: This observational analytical study employed a cross-sectional design. The sample comprised high school and vocational high school students selected by their schools to participate in data collection and complete the questionnaire fully. Data were gathered using a structured questionnaire assessing knowledge and attitudes toward STI laboratory testing. Analyses evaluated differences by school type, region, and gender. Results: No significant differences in knowledge or attitudes were identified by school type or geographic location. A significant difference emerged only in attitudes by sex, exhibiting a small effect size. Conclusion: The distribution of knowledge and attitudes indicates comparable levels of diagnostic literacy across schools and regions. Variation in attitudes by sex suggests differences in acceptance of laboratory examinations. Diagnostic literacy constitutes a critical component in enhancing laboratory-based early detection systems for STIs.